Use of low-intensity laser as a treatment for post-tooth whitening sensitivity: A literature review (Research, Society and Development, 2023)
Tooth whitening is the most conservative and least invasive treatment for changing dental color, gaining more and more space in aesthetic dentistry. However, its substances can cause adverse effects and the most common is tooth sensitivity. Low-intensity laser therapy is standing out in dentistry due to its analgesic property, helping to relieve pain. This work aims to conduct a literature review about low-intensity laser therapy used in the treatment of post-tooth whitening sensitivity. Its results are based on bibliographic searches in the electronic databases at Pub MED/Medline, Lilacs, and Scielo, in the period from 2017 to 2023. After the discussion of this work, the effectiveness of low-intensity therapy for the treatment of sensitivity was concluded, proving its reduction in cytotoxic effects, and can be considered an additional therapeutic alternative to the clinical procedure of tooth whitening.